2020
DOI: 10.1371/journal.pone.0239386
|View full text |Cite
|
Sign up to set email alerts
|

Circulating levels of microRNA193a-5p predict outcome in early stage hepatocellular carcinoma

Abstract: While tumor resection and liver transplantation (LT) represent potentially curative therapeutic options for patients with early-stage hepatocellular carcinoma (HCC), the identification of the ideal surgical candidates has remained challenging. Just recently, miRNA-193a-5p was described as a tumor suppressor in murine and human HCC but only little is known about circulating miRNA-193a-5p in HCC patients. Here, we evaluated serum levels of miR-193a-5p by qPCR in 41 HCC patients undergoing tumor resection (n = 33… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Interestingly, both groups demonstrated a comparable OS ( Fig 4A ). As the median might not be the optimal cut-off for the discrimination between patients with a favorable/unfavorable prognosis, we aimed at establishing a statistically optimal prognostic cut-off value by using a univariate binary cox proportional hazard model and testing for the minimum p-value as recently described [ 11 ]. By applying this cut-off value (9.82 relative units), we observed a strong trend towards an impaired survival in patients with miR-107 levels > 9.82, however the difference failed statistical significance (p = 0.119).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, both groups demonstrated a comparable OS ( Fig 4A ). As the median might not be the optimal cut-off for the discrimination between patients with a favorable/unfavorable prognosis, we aimed at establishing a statistically optimal prognostic cut-off value by using a univariate binary cox proportional hazard model and testing for the minimum p-value as recently described [ 11 ]. By applying this cut-off value (9.82 relative units), we observed a strong trend towards an impaired survival in patients with miR-107 levels > 9.82, however the difference failed statistical significance (p = 0.119).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the tumoral expression data suggesting a crucial role of miR-107 in HCC, we next aimed at measuring levels of circulating miR-107 in patients with early-stage HCC, representing the patient group being at highest need for the development of markers suitable for early detection of cancer. Between 2011 and 2017, we enclosed a total of n = 45 patients who presented with HCC and were allocated to either tumor resection (n = 37) or liver transplantation (LT, n = 8) [11]. The median age of the study population was 66 years (range: 42-82 years https://doi.org/10.1371/journal.pone.0247917.g001…”
Section: Baseline Characteristics Of Hcc Cohortmentioning
confidence: 99%
See 1 more Smart Citation
“…Loosen et al identified miRNA-193a-5p as a potential biomarker in the context of HCC as circulating relative miRNA-193a-5p levels were significantly elevated and predictive for patients’ outcome after tumor resection [ 61 ]. In line with this, Liu et al described a significant difference in miRNA-193-a-5p levels in serum of HCC patients compared to non-HCC patients, without any difference among patients with liver cirrhosis, chronic hepatitis B, and healthy controls [ 119 ].…”
Section: Specific Mirnas Involved In Hepatocarcinogenesismentioning
confidence: 99%
“…Low levels of miR-1, miR-122, miR-26a, miR-29a and miR-223-3p were associated with lower survival [ 50 , 51 , 52 , 56 ]. Patients with high levels of miR-155, miR-96 and miR-193-5p had lower survival rates [ 53 , 55 ]. A recent study reported whole miRNome profiling in 116 HCC patients [ 54 ].…”
Section: Introductionmentioning
confidence: 99%